Ethnogeographic approach to artisanal fishingin the Río Negro – Uruguay - Rodrigo Luan Childe Pereira; Marcel Achkar Borras; Cesar De David (Geografares, 2025)
Ethnogeography is a field of study that examines how human cultures interact with their geographic environments, analyzing the perceptions, uses, and meanings people attribute to a particular territory. This approach is applied to the study of artisanal fishing in the Río Negro, Uruguay, highlighting the social construction of the territory and the importance of local knowledge in the relationships between communities and the environment. The research draws on ethnogeographic fieldwork, analysis of local narratives, and historical investigation to examine the territorialities of artisanal fishing groups. The findings are organized into four dimensions: family and personal, socioeconomic and cultural, environmental and resource management, and the future of fishing. Results reveal that artisanal fishing is a family legacy central to the identity of fishers, despite persistent challenges such as environmental degradation, declining income, and the difficulty of transmitting knowledge to younger generations. Fishing communities demonstrate remarkable resilience and adaptability, continually seeking to achieve sustainability and protection of the ecosystems on which their lives and culture depend.